(3JQJjH KbGJ GdYLdis - (3Ydj Hf CHj HcQ Hf SdjeGf GdgjKej, CHh GdMSf, fhQ GdOjf, GdeUQj GdbGgQj,J (B807 (3g` s ((3SHW GHf GdYLei s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYdejf hCTgO Cf dG Edg EdG Gddg QH GdSehGJ hGdCQVjf s
(3BNQgG (B:s
(3hNTYJ GdCUhGJ ddQMef adG JSeY EdG geSkG GdBjI s
(3eQJH GdfSNI Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B45s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B91 s
Keywords: (3GdJGQjNs